Permission For Polygamy Because Teaching Islam To Converts From Maslahah Perspective: Study Decision No. 3728/PDT.G/2017/PA.DPK - Azis Dwi Utomo; Muh Zaitun Ardi; Nadyatul Hikmah Shuhufi (Universitas Muhammadiyah Palu, 2024)
This article discusses the considerations of the Depok religious court judge in granting permission for polygamy in case No. 3728/Pdt.G/2017/PA.Dpk. In this case, the applicant asked for permission to marry his partner, whom he married in an unregistered marriage in 2014. Previously, in 2003, this couple had been blessed with a child. they face legal problems to obtain their children's birth certificates; and this is one of the reasons the applicant applied for a polygamy permit. Even though this application does not meet the provisions of marriage law in Indonesia regarding the requirements for polygamy (Article 4 paragraph (2) Marriage Law No. 1/1974), the panel of judges in this case still granted permission for polygamy to the applicant. The consideration of the panel of judges was that the permission granted was of greater benefit than complying with the provisions of marriage law: legalizing unregistered marriages and the welfare of the child. This case once again shows that religious court judges are not only fixated on the provisions of positive law in Indonesia but also explore the laws that exist in society, including here the principles of sharia and fiqh.